Design of a low-voltage low-power CMOS phase detector for SONET/SDH standards - Wu, Rui (2008)
Due to the exponential growth in the Internet data traffic, the volume of data over the telecommunications network has increased rapidly. The required capacity of the transport (transmission) links must also increase, motivating work on faster communication channels. Among all the available transmission media, optical fiber achieves highest bandwidth with the lowest loss. Thus, the development of telecommunication transport networks has been accelerated, resulting in the Synchronous Optical Network (SONET)/Synchronous Digital Hierarchy (SDH) standards. The SONET OC-192, a standard for 10-Gb/s serial links, has been well established.